Impact of financial integration on economic development: a dynamic panel quantile regression analysis - Abdullahi, Abubakar; Ibrahim, Saifuzzaman; Hook, Law Siong; Wan Ngah, Wan Azman Saini (Center for Economic Integration, 2023)
This paper investigated the impact of financial integration on economic development using the dynamic panel quantile estimator on a sample of 95 countries from 2004-2019. The results showed that the impact of financial integration on economic development varied across income levels. This study found that financial integration impacted economic development negatively in middle and high-income countries. However, financial integration did not significantly affect economic development in low-income countries.